2011
DOI: 10.1109/lpt.2011.2138125
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Independent Curvature Sensor Using FBG Cladding Modes Based on a Core Misaligned Splice

Abstract: A fiber-optic curvature sensor based on a core offset single-mode fiber (SMF) combined with a fiber Bragg grating (FBG) is presented. The FBG cladding modes are efficiently excited by the large core misalignment. The curvature of the fiber can be obtained by the ratio between the recoupled cladding mode power and the reflected core mode power. These measurements are independent from temperature variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Changes in transmitted and reflected optical spectra can be used to interrogate physical and chemical parameters [69,70,71,72]. In order to improve the sensitivity of intensity-referenced sensors, diverse post-processing operations are utilized to couple light from the core mode into cladding modes [73,74,75,76]. These cladding modes have unique mode field shapes and distribution over the cross-section of fiber, and thus they can respond differently to perturbations within and outside the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in transmitted and reflected optical spectra can be used to interrogate physical and chemical parameters [69,70,71,72]. In order to improve the sensitivity of intensity-referenced sensors, diverse post-processing operations are utilized to couple light from the core mode into cladding modes [73,74,75,76]. These cladding modes have unique mode field shapes and distribution over the cross-section of fiber, and thus they can respond differently to perturbations within and outside the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The sensors are mainly based on fiber grating [1], multimode fiber (MMF) [2], and MachZehnder interferometer (MZI) [3,4], as examples. Among them, allfiber bending sensor plays an important role in fiber optic sensor field by monitoring the wavelength shift or energy variation in the transmission spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However most of these core-offset structures were used to act as sensing segments in the reported papers. [11][12][13][14][15][16] Cao et al reported a switchable dual-wavelength fiber laser based on core-offset structure. 17 This laser was fabricated by using a FBG in a core-offset structure.…”
Section: Introductionmentioning
confidence: 99%